(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Aleksandr Faynberg (1899-1968) taniqli rus shoiri va tarjimoni bo'lib, o'zining chuqur va introspektiv she'riyati bilan tanilgan. Yevropa va rus shoirlarining eng katta ijodiy tajribalari Faynberg she'riyatida mujassamlashgan. Qadimgi Sharq she'riyatining an'analari uning ixtirochilik uslubiga begona emas. .Ushbu maqolada mashhur shoir hisoblangan Aleksandr Faynberg haqida so'z yuritiladi Fainberg (1899-1968) was a notable Russian poet and translator known for his profound and introspective poetry.The greatest creative experiences of European and Russian poets are combined in Feinberg's poetry.The traditions of ancient Oriental poetry are not foreign to his inventive manner. This article is about the most famouse poet Aleksander Feinberg.